A self-limiting temperature graphene material and preparation method thereof

By using self -limited temperature graphene materials, the existing pavement melting ice and snow removal technology does not have the problem of self -temperature limit protection heating, realize the self -limiting function of the material, reduce costs and energy consumption, and improve the conductivity of the material. Performance and durability.

CN118909491BActive Publication Date: 2025-01-28FUJIAN JIUXIN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411405731.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-28
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing road surface ice melting and snow removal technology does not have the function of self-limiting temperature protection heating, and is cost-effective and inefficient.

Method used

The material is used for self-limited temperature graphene material. This material consists of graphene radiotherapy material, modified carbon fiber, multi-wall carbon nanotuba, ethylene-acetate-ethylene symbol, laurein acid, adhesive, and plasticizer. Methods and composition proportions to realize the self -limiting function of materials.

Benefits of technology

The automatic control of the temperature and high energy consumption problems caused by the automatic control temperature during the snow melting process can be achieved, and it has the advantages of low cost and simple and easy -to -run, and at the same time improve the conductive performance and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of snow melting and deicing, and provides a self-limiting temperature graphene material and a preparation method thereof, so as to solve the defects that the existing road ice melting and snow removal technology does not have the function of self-limiting temperature protection heating, and has high cost and low efficiency; the material comprises the following raw materials in parts by weight: 5-10 parts by weight of graphene-based thermal conductive material, 2-5 parts by weight of modified carbon fiber, 2-5 parts by weight of multi-walled carbon nanotubes, 15-30 parts by weight of ethylene-vinyl acetate copolymer, 30-60 parts by weight of lauric acid, 8-15 parts by weight of binder and 5-10 parts by weight of plasticizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of snow melting and deicing, and in particular to a self-limiting temperature graphene material and a preparation method thereof. Background Art

[0002] With the impact of global climate change, winter weather is getting colder and colder, and the problem of snow and ice on the road is becoming more and more serious. According to the survey, the friction coefficient of normal dry asphalt road is 0.6, the friction coefficient of rainy road is reduced to 0.4, the friction coefficient of snowy road is 0.28, and the icy road is only 0.18. Therefore, the braking distance of icy road is much longer than that of normal dry or even rainy road, which poses a serious safety hazard. In order to ensure the safety and smoothness of road traffic, efficient road snow melting and ice removal technology is crucial.

[0003] At present, the methods of road ice melting and snow removal mainly include: traditional artificial snow removal, snow removal with snow melting agent, and heating ice melting and snow removal. Although the traditional artificial snow removal method can remove ice and snow well, it is time-consuming and labor-intensive, and affects the road traffic capacity; and the use of snow melting agent to remove snow seriously pollutes the environment, destroys the acid-base balance of the soil, corrodes road facilities, and causes road cracks. To solve the above problems, heating ice melting and snow removal is currently a more effective method. Chinese patent publication number CN110468653B discloses a graphene ultra-thin conductive wear layer construction method, and the key points of its technical solution are construction preparation, power cable installation, sensor burial and installation, control system installation, control system installation in the control box, leveling layer laying, paving insulation layer, laying graphene heating layer, paving surface wear layer, maintenance, maintenance after construction is completed, system debugging and inspection, after the system is fully installed, system debugging, quality inspection and acceptance, and opening traffic after the effective strength is formed and stabilized, generally 30 hours after paving. This graphene ultra-thin conductive wear layer construction method has the advantages of rapid snow removal and reduced corrosion. However, this invention has the problem of damaging the power cables when the heating temperature is too high, and has high energy consumption and does not have the characteristics of intelligent energy saving.

[0004] Chinese patent publication number CN114657838B discloses an intelligent energy-saving snow-melting pavement and manufacturing method of a flexible electronic heating cable, which solves the technical problems of insufficient toughness and large power loss of cables in existing technical methods. The flexible cable is made of special modified multi-walled carbon nanotubes, so that the cable has good bending, elasticity and hydrophobicity; the cable is heated and the power is adjusted in real time by analyzing the data obtained by algorithms such as image fusion, Kalman filtering and visual detection, and the snow on the road is cleared with the lowest heating energy consumption. On the one hand, the invention uses special materials to make the flexible cable so that the load bearing capacity and fatigue load resistance of the heating cable such as wheels are stronger, ensuring the durability of the asphalt embedded cable. On the other hand, it can achieve zero snow accumulation on the road through visual detection intelligent detection technology combined with real-time engineering backgrounds such as wheel rolling and lighting under almost zero interference. However, the invention does not have the function of self-limiting temperature protection cable when melting snow, and the application of algorithms such as image fusion, Kalman filtering and visual detection requires the cooperation of servers, which is costly. Summary of the invention

[0005] Therefore, in view of the above problems, the present invention provides a self-limiting temperature graphene material and a preparation method thereof, so as to solve the defects that the existing road ice melting and snow removal technology does not have the function of self-limiting temperature protection heating, and has high cost and low efficiency.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A self-limiting temperature graphene material comprises the following raw materials in parts by weight: 5-10 parts by weight of graphene-based thermal conductive material, 2-5 parts by weight of modified carbon fiber, 2-5 parts by weight of multi-walled carbon nanotubes, 15-30 parts by weight of ethylene-vinyl acetate copolymer, 30-60 parts by weight of lauric acid, 8-15 parts by weight of binder and 5-10 parts by weight of plasticizer;

[0008] Wherein, the preparation process of the graphene-based thermal conductive material is:

[0009] a. Weigh 5-8 parts by weight of graphite, wash it 3-5 times with a dilute HCl solution, and then wash it 3-5 times with deionized water. After drying at 90°C-100°C for 6h-8h, add concentrated sulfuric acid in a ratio of 1:20-1:25 between the solid and liquid ratio of graphite and concentrated sulfuric acid, stir at a speed of 20r / min-30r / min for 30min-45min under an ice water bath at 0°C-10°C, and then add an oxidant in a ratio of 1:3-4 between the weight ratio of graphite and the oxidant, increase the water bath temperature to 30°C-35°C, and keep it for 30min-45min to obtain a first mixed solution;

[0010] b. Then, under the condition of an ice water bath at 0°C-10°C, deionized water is added to the first mixed solution in a ratio of 1:3-1:5 to the first mixed solution, the water bath temperature is increased to 80°C-90°C, and the mixture is stirred at a speed of 20r / min-30r / min for 30min-45min to obtain a second mixed solution, and H2O2 solution is added dropwise to the second mixed solution in a ratio of 1:10-1:15 by volume to the second mixed solution, and the mixture is stirred evenly at a speed of 20r / min-30r / min, and then allowed to stand for stratification;

[0011] c. Remove the supernatant, wash the lower turbid liquid with dilute HCl solution and deionized water for 3-5 times in sequence, then evaporate it, dry it at 90-100°C for 6-8h, peel it off and perform hot pressing reduction reaction, cool it to room temperature under argon atmosphere to obtain graphene oxide film, make the graphene oxide film into powder, and obtain the graphene-based thermal conductive material.

[0012] Furthermore, the preparation process of the modified carbon fiber is as follows: the polyacrylonitrile-based carbon fiber is immersed in an acetone solution for 40h-48h, dried at 90℃-100℃ for 6h-8h, treated with a KMnO4 solution with a mass fraction of 6wt%-10wt% for 3min-5min in a water bath at 80℃-85℃, and then dried at 90℃-100℃ for 6h-8h to obtain the modified carbon fiber.

[0013] Furthermore, the purity of the multi-walled carbon nanotubes is greater than 95wt%, the inner diameter is 3nm-5nm, the outer diameter is 8nm-15nm, and the length is 3 m m-8 m m; the plasticizer is dioctyl phthalate; the binder is any one of epoxy resin, polyurethane and water-based acrylic resin.

[0014] Furthermore, the particle size of the graphene-based thermal conductive material is 30nm-45nm.

[0015] Furthermore, the mesh size of the graphite is 325-500 mesh; the concentration of the dilute HCl solution is 5%-10%; the oxidant is KMnO4; and the concentration of the H2O2 solution is 25%-30%.

[0016] Furthermore, the evaporation treatment is carried out in an evaporation tank at a temperature of 60°C-80°C; the hot pressing reduction reaction is: under the protection of an argon atmosphere with a gas flow rate of 50ml / min-55ml / min, the temperature is increased from 25°C to 100°C at a heating rate of 2.5°C / min, then the temperature is increased to 300°C at a heating rate of 1.11°C / min, and then the temperature is heated to 800°C at a heating rate of 8.33°C / min, and kept warm for 2h-2.5h.

[0017] Furthermore, the length of the polyacrylonitrile-based carbon fiber is 2 mm to 5 mm, and the diameter is 5 m m-8 m m.

[0018] A method for preparing a self-limiting temperature graphene material comprises the following steps:

[0019] S1. Weigh the graphene-based thermal conductive material, modified carbon fiber and multi-walled carbon nanotubes according to the above weight parts, add anhydrous ethanol and sodium hexametaphosphate, stir at a speed of 1000 r / min-1200 r / min for 10 min-20 min, perform ultrasonic dispersion, and dry at 90° C.-100° C. for 1 h-2 h to obtain a mixture for standby use;

[0020] S2. Weigh ethylene-vinyl acetate copolymer and lauric acid according to the above weight parts, add xylene solution, stir at a speed of 20r / min-30r / min for 10min-15min in a water bath at 80°C-90°C, mix well, and obtain a mixed solution for standby use;

[0021] S3. Add the mixture obtained in step S1 to the mixed solution obtained in step S2, add a binder and a plasticizer according to the above weight portions, stir at a speed of 1000 r / min-1200 r / min for 10 min-20 min, and ultrasonically disperse to obtain the self-limiting temperature graphene material.

[0022] Furthermore, the ultrasonic dispersion is carried out in an ultrasonic disperser at a frequency of 30 KHz-40 KHz and a time of 10 min-15 min.

[0023] By adopting the above technical solution, the beneficial effects of the present invention are:

[0024] Among the raw materials adopted in the present invention, the graphene-based thermal conductive material uses graphite as one of the raw materials and is prepared by a carbonization temperature thermal reduction process. It has the characteristics of high electrical and thermal conductivity, large output, is suitable for large-scale production and application to snow melting and ice removal on the road surface, and has low preparation cost and simple preparation method; at the same time, the modified carbon fiber used as the raw material is not easy to knot and agglomerate in the process of preparing the self-limiting temperature graphene material, and not only has good electrical conductivity, high temperature resistance, friction resistance, corrosion resistance, and good chemical stability, but also can improve the strength of the self-limiting temperature graphene material and resist wheel rolling; multi-walled carbon nanotubes not only have good electrical conductivity, but also have good bending, elasticity and hydrophobicity, so that the prepared self-limiting temperature graphene material can be adapted to various road surfaces.

[0025] The resistivity of a positive temperature coefficient (PTC) material remains essentially unchanged in the low temperature region. When a certain temperature is exceeded, its resistivity increases rapidly by several orders of magnitude (10 3 ~10 5 ), then, the resistivity increases slowly or steadily, that is, it reaches the termination point. This phenomenon is called the PTC effect of the material, and the specific temperature point corresponds to the Curie temperature of the material. In the present invention, ethylene-vinyl acetate copolymer with low crystallinity is used as the skeleton material, and organic acid crystal lauric acid with low melting point and similar structure to ethylene-vinyl acetate copolymer is used as the temperature control material of the Curie temperature point. The Curie temperature of the prepared self-limiting temperature graphene material is about 60°C. After being heated, it has a low resistance, thereby generating heat and transferring the heat to the road surface. Since the temperature of the road surface is higher than the ambient temperature, the road surface is melted and snow is removed; when the temperature rises above the Curie temperature, the heating power of the self-limiting temperature graphene material drops rapidly due to its sharp increase in resistance, thereby stabilizing the controlled temperature near its Curie temperature, thereby realizing the self-limiting temperature function. This temperature control method does not require the installation of an anti-overheating device or an additional control system, can reduce the complexity and energy consumption of the temperature control system, and has the advantages of low cost and simplicity. DETAILED DESCRIPTION

[0026] Example 1

[0027] A method for preparing a self-limiting temperature graphene material comprises the following steps:

[0028] (1) Selection of raw materials: 5 parts by weight of graphene-based thermal conductive material, 2 parts by weight of modified carbon fiber, 2 parts by weight of multi-walled carbon nanotubes, 15 parts by weight of ethylene-vinyl acetate copolymer, 30 parts by weight of lauric acid, 8 parts by weight of water-based acrylic resin, and 5 parts by weight of dioctyl phthalate;

[0029] The purity of the multi-walled carbon nanotubes is greater than 95wt%, the inner diameter is 3nm, the outer diameter is 8nm, and the length is 3 m m;

[0030] (2) Preparation of graphene-based thermal conductive materials:

[0031] a. Weigh 5 parts by weight of 325-mesh graphite, wash it three times in a 5% dilute HCl solution, then wash it three times with deionized water, dry it at 90°C for 6 hours, add concentrated sulfuric acid in a ratio of 1:20 between graphite and concentrated sulfuric acid, stir it at a speed of 20 r / min for 30 minutes in an ice-water bath at 0°C, then add KMnO4 in a ratio of 1:3 between graphite and KMnO4, raise the water bath temperature to 30°C, and keep it for 30 minutes to obtain a first mixed solution;

[0032] b. Then, under the condition of an ice water bath at 0°C, deionized water was added to the first mixed solution in a ratio of 1:3 between the first mixed solution and deionized water, the water bath temperature was raised to 80°C, and the mixture was stirred at a speed of 20 r / min for 30 min to obtain a second mixed solution, and a 25% H2O2 solution was added dropwise to the second mixed solution in a ratio of 1:10 by volume of the H2O2 solution and the second mixed solution, and the mixture was stirred evenly at a speed of 20 r / min, and then allowed to stand for stratification;

[0033] c. Remove the supernatant, wash the lower turbid liquid with a 5% dilute HCl solution and deionized water for three times, evaporate in an evaporation tank at 60°C, dry at 90°C for 6 hours, peel off, and perform hot pressing reduction reaction. Under the protection of an argon atmosphere with a gas flow rate of 50 ml / min, heat from 25°C to 100°C at a heating rate of 2.5°C / min, then heat to 300°C at a heating rate of 1.11°C / min, and then heat to 800°C at a heating rate of 8.33°C / min, keep warm for 2 hours, and cool to room temperature under the protection of an argon atmosphere to obtain a graphene oxide film, and make the graphene oxide film into a powder to obtain the graphene-based thermal conductive material with a particle size of 30 nm;

[0034] (3) Preparation of modified carbon fiber:

[0035] The length is 2mm and the diameter is 5 m The polyacrylonitrile-based carbon fiber of m is immersed in an acetone solution for 48 hours, dried at 90° C. for 6 hours, treated with a KMnO4 solution with a mass fraction of 6wt% for 3 minutes in a water bath at 80° C., and dried at 90° C. for 8 hours to obtain the modified carbon fiber;

[0036] (4) Preparation of self-limiting temperature graphene materials:

[0037] S1. Weigh the graphene-based thermal conductive material, modified carbon fiber, and multi-walled carbon nanotubes according to the above weight parts, add anhydrous ethanol and sodium hexametaphosphate, stir at a speed of 1200 r / min for 10 min, perform ultrasonic dispersion, and dry at 90° C. for 2 h to obtain a mixture for standby use;

[0038] S2. Weigh ethylene-vinyl acetate copolymer and lauric acid according to the above weight parts, add xylene solution, stir at a speed of 20 r / min for 10 min in a water bath at 80° C., mix well, and obtain a mixed solution for standby use;

[0039] S3. Add the mixture obtained in step S1 to the mixed solution obtained in step S2, add water-based acrylic resin and dioctyl phthalate according to the above weight parts, stir at a speed of 1200r / min for 10min, and perform ultrasonic dispersion in an ultrasonic disperser at a frequency of 30KHz for 10min to obtain the self-limiting temperature graphene material.

[0040] The self-limiting temperature graphene material obtained above was tested, and the specific testing process was as follows:

[0041] (5-1) Install wires at both ends and in the middle of a polished thin copper sheet electrode with a size of 10 mm × 300 mm, and weld the copper core wire to the electrode sheet. Coat one side of the electrode sheet with epoxy resin and adhere it to both sides of an asphalt concrete slab with a size of 300 mm × 150 mm × 100 mm. After the epoxy resin solidifies, polish the electrode plate again with coarse sandpaper.

[0042] (5-2) coating an acrylic resin layer on an asphalt concrete slab, and applying the self-limiting temperature graphene material obtained in step (4) on the surface of the acrylic resin layer to a thickness of 6 mm to form a conductive functional layer; and paving a black corundum crushed stone layer on the surface of the conductive functional layer by a full spreading method to a thickness of 3 mm. The layer was allowed to completely solidify for 3 days, and the surface was cleaned of more black corundum crushed stone. Three groups of molding samples were prepared according to the above method and were numbered A, B, and C respectively;

[0043] (5-3) Using a digital multimeter with an accuracy of 0.1%, the resistance of the molded sample obtained in (5-2) was tested, and the resistivity was calculated based on the size of the molded sample;

[0044] (5-4) The samples of composition A were placed in a 60℃ water bath, and the samples of composition B were placed in a -20℃ refrigerator. After 24 hours, their resistances were measured respectively. Then, the samples of composition A were placed in a -20℃ refrigerator, and the samples of composition B were placed in a 60℃ water bath. After 24 hours, their resistivities were measured respectively. The steps were repeated for 3 cycles to test the resistivity during the freeze-thaw cycle. The samples of composition C were not treated in any way.

[0045] (5-5) The three groups of molded samples were placed in the test tank of the MMLS3 small accelerated loading equipment in turn. After loading for 1 million times, the friction pendulum values ​​of the specimens were tested respectively. The measurement results are shown in Table 1.

[0046] Table 1 Test data of the three groups of samples in Example 1 during freeze-thaw cycles

[0047]

[0048] It can be seen from the test data in Table 1 that the resistivity of the molded samples prepared by the self-limiting temperature graphene material of the present invention is at a low level, showing that its electrical conductivity is high and its conductive performance is excellent; the data of the control group C show that at 25°C, the conductive performance of the molded samples remains stable; during the three freeze-thaw cycles, the resistivity fluctuation of the molded samples is very small, indicating that the resistivity performance of the molded samples is good under the freeze-thaw environment; the resistivity of the molded samples is low under negative temperature conditions, and the resistivity of the molded samples is high under positive temperature conditions, indicating that the molded samples have a positive temperature coefficient effect. After loading 1 million times, the friction pendulum value of the untreated C group molded samples decreased from the initial 68 BPN to 63 BPN; after loading 1 million times, the friction pendulum values ​​of the A group and B group molded samples decreased from 64 BPN and 68 BPN to 57 BPN and 61 BPN respectively, and the anti-slip attenuation amplitude was small, indicating that the molded samples of the present invention have good anti-slip durability.

[0049] Example 2

[0050] A method for preparing a self-limiting temperature graphene material comprises the following steps:

[0051] (1) Selection of raw materials: 8 parts by weight of graphene-based thermal conductive material, 3 parts by weight of modified carbon fiber, 3 parts by weight of multi-walled carbon nanotubes, 20 parts by weight of ethylene-vinyl acetate copolymer, 40 parts by weight of lauric acid, 10 parts by weight of epoxy resin, and 8 parts by weight of dioctyl phthalate;

[0052] The purity of the multi-walled carbon nanotubes is greater than 95wt%, the inner diameter is 5nm, the outer diameter is 10nm, and the length is 5 m m;

[0053] (2) Preparation of graphene-based thermal conductive materials:

[0054] a. Weigh 5 parts by weight of 325-mesh graphite, wash it three times in a dilute HCl solution with a concentration of 8%, then wash it three times with deionized water, dry it at 90°C for 8 hours, add concentrated sulfuric acid in a ratio of 1:20 between the solid and liquid ratio of graphite and concentrated sulfuric acid, stir it at a speed of 20 r / min for 30 minutes in an ice-water bath at 0°C, then add KMnO4 in a ratio of 1:3 between the weight ratio of graphite and KMnO4, raise the water bath temperature to 30°C, and keep it for 30 minutes to obtain a first mixed solution;

[0055] b. Then, under the condition of an ice water bath at 0°C, deionized water was added to the first mixed solution in a ratio of 1:5, the water bath temperature was raised to 80°C, and the mixture was stirred at a speed of 20 r / min for 30 min to obtain a second mixed solution, and a 30% H2O2 solution was added dropwise to the second mixed solution in a ratio of 1:15 by volume of the H2O2 solution to the second mixed solution, and the mixture was stirred evenly at a speed of 20 r / min, and then allowed to stand for stratification;

[0056] c. Remove the supernatant, wash the lower turbid liquid with 8% dilute HCl solution and deionized water three times in sequence, evaporate in an evaporation tank at 70°C, dry at 90°C for 8h, peel off, and perform hot pressing reduction reaction. Under the protection of an argon atmosphere with a gas flow rate of 55ml / min, heat from 25°C to 100°C at a heating rate of 2.5°C / min, then heat to 300°C at a heating rate of 1.11°C / min, and then heat to 800°C at a heating rate of 8.33°C / min, keep warm for 2.5h, and cool to room temperature under the protection of an argon atmosphere to obtain a graphene oxide film, and make the graphene oxide film into a powder to obtain the graphene-based thermal conductive material with a particle size of 35nm;

[0057] (3) Preparation of modified carbon fiber:

[0058] The length is 5mm and the diameter is 8 m The polyacrylonitrile-based carbon fiber of m is immersed in an acetone solution for 48 hours, dried at 90° C. for 8 hours, treated with a KMnO4 solution with a mass fraction of 10wt% for 3 minutes in a water bath at 80° C., and dried at 90° C. for 8 hours to obtain the modified carbon fiber;

[0059] (4) Preparation of self-limiting temperature graphene materials:

[0060] S1. Weigh the graphene-based thermal conductive material, modified carbon fiber, and multi-walled carbon nanotubes according to the above weight parts, add anhydrous ethanol and sodium hexametaphosphate, stir at a speed of 1200 r / min for 15 min, perform ultrasonic dispersion, and dry at 90° C. for 2 h to obtain a mixture for standby use;

[0061] S2, weighing ethylene-vinyl acetate copolymer and lauric acid according to the above weight parts, adding xylene solution, stirring at a speed of 20r / min for 10min in a water bath at 90°C, mixing evenly, obtaining a mixed solution, and setting aside;

[0062] S3, adding the mixture obtained in step S1 to the mixed solution obtained in step S2, adding epoxy resin and dioctyl phthalate according to the above weight parts, stirring at a speed of 1200r / min for 15min, and performing ultrasonic dispersion in an ultrasonic disperser at a frequency of 35KHz for 12min to obtain the self-limiting temperature graphene material;

[0063] The self-limiting temperature graphene material obtained above was tested: the testing method was the same as the steps in Example 1, and only the C-component sample without any treatment was obtained.

[0064] Example 3

[0065] A method for preparing a self-limiting temperature graphene material comprises the following steps:

[0066] (1) Selection of raw materials: 10 parts by weight of graphene-based thermal conductive material, 5 parts by weight of modified carbon fiber, 5 parts by weight of multi-walled carbon nanotubes, 30 parts by weight of ethylene-vinyl acetate copolymer, 60 parts by weight of lauric acid, 15 parts by weight of adhesive polyurethane, and 10 parts by weight of dioctyl phthalate;

[0067] The purity of the multi-walled carbon nanotubes is greater than 95wt%, the inner diameter is 5nm, the outer diameter is 15nm, and the length is 8 m m;

[0068] (2) Preparation of graphene-based thermal conductive materials:

[0069] a. Weigh 8 parts by weight of 500-mesh graphite, wash it three times with a 10% dilute HCl solution, then wash it three times with deionized water, dry it at 100°C for 6 hours, add concentrated sulfuric acid in a ratio of 1:25 between the solid and liquid ratio of graphite and concentrated sulfuric acid, stir it at a speed of 20 r / min for 30 minutes in an ice-water bath at 0°C, then add KMnO4 in a ratio of 1:4 between the weight ratio of graphite and KMnO4, raise the water bath temperature to 35°C, and keep it for 45 minutes to obtain a first mixed solution;

[0070] b. Then, under the condition of an ice water bath at 0°C, deionized water was added to the first mixed solution in a ratio of 1:5, the water bath temperature was raised to 90°C, and the mixture was stirred at a speed of 30 r / min for 45 min to obtain a second mixed solution. A 30% H2O2 solution was added dropwise to the second mixed solution in a volume ratio of 1:15 between the H2O2 solution and the second mixed solution, and the mixture was stirred evenly at a speed of 30 r / min, and then allowed to stand for stratification;

[0071] c. Remove the supernatant, wash the lower turbid liquid with a 10% dilute HCl solution and deionized water for three times, evaporate in an evaporation tank at 80°C, dry at 100°C for 6 hours, peel off, and perform hot pressing reduction reaction. Under the protection of an argon atmosphere with a gas flow rate of 50 ml / min, heat from 25°C to 100°C at a heating rate of 2.5°C / min, then heat to 300°C at a heating rate of 1.11°C / min, and then heat to 800°C at a heating rate of 8.33°C / min, keep warm for 2.5 hours, and cool to room temperature under the protection of an argon atmosphere to obtain a graphene oxide film, and make the graphene oxide film into a powder to obtain the graphene-based thermal conductive material with a particle size of 45 nm;

[0072] (3) Preparation of modified carbon fiber:

[0073] The length is 5mm and the diameter is 8 m The polyacrylonitrile-based carbon fiber of m is immersed in an acetone solution for 48 hours, dried at 100° C. for 6 hours, treated with a KMnO4 solution with a mass fraction of 10wt% for 3 minutes in a water bath at 85° C., and dried at 100° C. for 6 hours to obtain the modified carbon fiber;

[0074] (4) Preparation of self-limiting temperature graphene materials:

[0075] S1. Weigh the graphene-based thermal conductive material, modified carbon fiber, and multi-walled carbon nanotubes according to the above weight parts, add anhydrous ethanol and sodium hexametaphosphate, stir at a speed of 1000 r / min for 20 min, perform ultrasonic dispersion, and dry at 100° C. for 1 h to obtain a mixture for standby use;

[0076] S2. Weigh ethylene-vinyl acetate copolymer and lauric acid according to the above weight parts, add xylene solution, stir at a speed of 30 r / min for 10 min in a water bath at 90° C., mix well, and obtain a mixed solution for standby use;

[0077] S3, adding the mixture obtained in step S1 to the mixed solution obtained in step S2, adding polyurethane and dioctyl phthalate according to the above weight parts, stirring at a speed of 1000r / min for 20min, and performing ultrasonic dispersion in an ultrasonic disperser at a frequency of 40KHz for 10min to obtain the self-limiting temperature graphene material;

[0078] The self-limiting temperature graphene material obtained above was tested: the testing method was the same as the steps in Example 1, and only the C-component sample without any treatment was obtained.

[0079] Example 4

[0080] The application of the self-limiting temperature graphene material in road snow melting and ice removal comprises the following steps:

[0081] A 2 mm thick acrylic resin layer is applied on the asphalt pavement, and then the self-limiting temperature graphene material obtained in Example 1 is applied to the surface of the acrylic resin layer with a thickness of 6 mm. During the application process, the surface is ensured to be flat and free of potholes to form a conductive functional layer. A 3 mm thick black corundum gravel layer is laid on the surface of the conductive functional layer by a full spreading method, and the layer is waited for complete curing for 3 days, and more black corundum gravel is removed from the surface.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that ethylene-vinyl acetate copolymer and lauric acid are not added as raw materials, and the conductive material is a commercially known carbon powder. The same binder and plasticizer as in Example 1 are used. Other technical solutions are the same as in Example 1. In the self-limiting temperature graphene material test, the steps are the same as in Example 1, and only the C-component type sample without any treatment is obtained.

[0084] Table 2 Temperature and power changes of the C composition samples of Example 1, Example 2, Example 3 and Comparative Example 1 under continuous heating

[0085]

[0086] It can be seen from Table 2 that the power of the molded samples of Example 1, Example 2, and Example 3 did not change at 60°C, indicating that the PTC effect material of the molded samples at this time has not reached the softening point, so it will not prevent the formation of conductive paths of materials such as graphene-based thermal conductive materials, modified carbon fibers, and multi-walled carbon nanotubes, and the temperature is lower than the Curie temperature at this time; at 80°C and 100°C, the power of the molded samples of Example 1, Example 2, and Example 3 all showed a significant decrease, indicating that the PTC effect material of the molded samples of Example 1, Example 2, and Example 3 can soften at this time, and the material wraps the conductive powder to prevent the formation of the conductive path, thereby disconnecting the circuit, and the temperature begins to automatically decrease to achieve self-limiting temperature; while the power of the molded sample of Comparative Example 1 at 60°C, 80°C, and 100°C all showed an increase, and the higher the temperature, the greater the increase. This shows that the conductive performance of the molded sample without adding the material with PTC effect increases with the increase of temperature, which is prone to local overheating.

[0087] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. A self-limiting temperature graphene material, characterized in that: The invention comprises the following raw materials in parts by weight: 5-10 parts by weight of graphene-based thermal conductive material, 2-5 parts by weight of modified carbon fiber, 2-5 parts by weight of multi-walled carbon nanotubes, 15-30 parts by weight of ethylene-vinyl acetate copolymer, 30-60 parts by weight of lauric acid, 8-15 parts by weight of binder and 5-10 parts by weight of plasticizer; Wherein, the preparation process of the graphene-based thermal conductive material is: a. Weigh 5-8 parts by weight of graphite, wash it 3-5 times with a dilute HCl solution, and then wash it 3-5 times with deionized water. After drying at 90°C-100°C for 6h-8h, add concentrated sulfuric acid in a ratio of 1:20-1:25 between the solid and liquid ratio of graphite and concentrated sulfuric acid, stir at a speed of 20r / min-30r / min for 30min-45min under an ice water bath at 0°C-10°C, and then add an oxidant in a ratio of 1:3-1:4 between the weight ratio of graphite and the oxidant, raise the water bath temperature to 30°C-35°C, and keep it for 30min-45min to obtain a first mixed solution; b. Then, under the condition of an ice water bath at 0°C-10°C, deionized water is added to the first mixed solution in a ratio of 1:3-1:5 to the first mixed solution, the water bath temperature is increased to 80°C-90°C, and the mixture is stirred at a speed of 20r / min-30r / min for 30min-45min to obtain a second mixed solution, and H2O2 solution is added dropwise to the second mixed solution in a ratio of 1:10-1:15 by volume to the second mixed solution, and the mixture is stirred evenly at a speed of 20r / min-30r / min, and then allowed to stand for stratification; c. Remove the supernatant, wash the lower turbid liquid with dilute HCl solution and deionized water for 3-5 times in sequence, then evaporate it, dry it at 90-100°C for 6-8h, peel it off and perform hot pressing reduction reaction, cool it to room temperature under argon atmosphere to obtain graphene oxide film, make the graphene oxide film into powder, and obtain the graphene-based thermal conductive material.

2. A self-temperature limiting graphene material according to claim 1, characterized in that: The preparation process of the modified carbon fiber is as follows: the polyacrylonitrile-based carbon fiber is immersed in an acetone solution for 40h-48h, dried at 90°C-100°C for 6h-8h, treated with a KMnO4 solution with a mass fraction of 6wt%-10wt% for 3min-5min in a water bath at 80°C-85°C, and then dried at 90°C-100°C for 6h-8h to obtain the modified carbon fiber.

3. A self-temperature limiting graphene material according to claim 1, characterized in that: The purity of the multi-walled carbon nanotubes is greater than 95wt%, the inner diameter is 3nm-5nm, the outer diameter is 8nm-15nm, and the length is 3μm-8μm; the plasticizer is dioctyl phthalate; and the binder is any one of epoxy resin, polyurethane and water-based acrylic resin.

4. The self-temperature-limiting graphene material according to claim 1, characterized in that: The particle size of the graphene-based thermal conductive material is 30nm-45nm.

5. The self-temperature-limiting graphene material according to claim 1, characterized in that: The mesh size of the graphite is 325-500 mesh; the concentration of the dilute HCl solution is 5%-10%; the oxidant is KMnO4; and the concentration of the H2O2 solution is 25%-30%.

6. The self-temperature-limiting graphene material according to claim 1, characterized in that: The evaporation treatment is carried out in an evaporation tank at a temperature of 60°C-80°C; the hot pressing reduction reaction is: under the protection of an argon atmosphere with a gas flow rate of 50ml / min-55ml / min, the temperature is increased from 25°C to 100°C at a heating rate of 2.5°C / min, then the temperature is increased to 300°C at a heating rate of 1.11°C / min, and then the temperature is heated to 800°C at a heating rate of 8.33°C / min, and kept warm for 2h-2.5h.

7. The self-temperature-limiting graphene material according to claim 2, characterized in that: The polyacrylonitrile-based carbon fiber has a length of 2 mm to 5 mm and a diameter of 5 μm to 8 μm.

8. A method for preparing a self-temperature-limiting graphene material as claimed in claim 1, characterized in that: The following steps are involved: S1. Weigh the graphene-based thermal conductive material, modified carbon fiber and multi-walled carbon nanotubes according to the weight parts of claim 1, add anhydrous ethanol and sodium hexametaphosphate, stir at a speed of 1000 r / min-1200 r / min for 10 min-20 min, perform ultrasonic dispersion, dry at 90° C.-100° C. for 1 h-2 h, obtain a mixture, and set aside; S2. Weigh the ethylene-vinyl acetate copolymer and lauric acid in parts by weight according to claim 1, add xylene solution, stir at a speed of 20 r / min-30 r / min for 10 min-15 min in a water bath at 80° C.-90° C., mix well, and obtain a mixed solution for standby use; S3. Add the mixture obtained in step S1 to the mixed solution obtained in step S2, add a binder and a plasticizer in proportion by weight according to claim 1, stir at a speed of 1000 r / min-1200 r / min for 10 min-20 min, and perform ultrasonic dispersion to obtain the self-limiting temperature graphene material.

9. The method for preparing a self-temperature-limiting graphene material according to claim 8, characterized in that: The ultrasonic dispersion is carried out in an ultrasonic disperser at a frequency of 30 KHz-40 KHz and a time of 10 min-15 min.

Citation Information

Patent Citations

  • A method for constructing an ultrathin conductive wear layer of graphene

    CN110468653B

  • A smart energy-saving snow-melting pavement using a flexible electronic heating cable and its manufacturing method

    CN114657838B

  • Graphene heat-dissipation coating material, preparation method and applications thereof

    CN108690454A

  • Conductive micro-powder for polymer-based PTC (Positive Temperature Coefficient) material, preparation method of conductive micro-powder and PTC self-temperature-control coating

    CN115595008A